Europejka - Gretkowska, Manuela (Warszawa : Wydawn. W.A.B, 2004)
The diary of a young woman who returns to Poland from Europe, at the period when Poland is returning to Europe. She writes about people and personalities she meets, while living in a village which is a suburb of Warsaw.
Keywords: Poland -- Fiction